Erectile dysfunction and health-related quality of life in elderly males - Asmara, Kirana; Marisha, Meitty; Hengky, Hengky; Agustanti, Fitria; Tampubolon, Hotma P. (Faculty of Medicine, Trisakti University, 2011)
One important aspect that will determine the quality of human life is sex life. Therefore sexual activity may be used in the assessment of the quality of life. Erectile dysfunction (ED) is the inability to continuously achieve or maintain a penile erection quality so as to achieve a satisfying sexual relationship. The aim of this study was to determine the relationship between ED and quality of life in the male elderly. A cross-sectional study was carried out on males aged 60 years and over in West Cilandak village, South Jakarta. The presence of ED was evaluated by means of the International Index of Erectile Function (IIEF) and quality of life with the Short Form Health Survey (SF-36). One-way analysis of variance (ANOVA) was used to compare the mean difference of QOL by erectile dysfunction category. The correlation between the total ED scoreÂ and QOL was analyzed using the Pearson correlation analysis. Subjects included 199 elderly male patients, with mean age of 66.7 years (age range 60-81 years), among whom 80.5% presented with ED. The results of ANOVA analysis showed that ED affects quality of life total score (p=0.000), with a significant difference in the vitality (p=0.029), physical functionÂ (p=0.048), and role emotional subscales (p=0.011). ED is a highly prevalent among elderly males and impairs the overall quality of life, The SF-36 is applicable and suitable for evaluation of quality of life.